PERJANJIAN PENAMBANGAN BATU BARA ANTARA SUKU NAN BALIMO KOLOK NAN TUO DENGAN CV. TAHITI COAL DIDAERAH SANGKAR PUYUH DESA KOLOK KECAMATAN BARANGIN KOTA SAWAHLUNTO - Wulan Tri Suryani dan Yevendri (Normative Jurnal Ilmiah Hukum, 2019)
Indonesia is one of the biggest coal mining producing countries in the world. Rapid growth is not matched by good management by irresponsible parties. Coal has an important role in fulfilling the lives of many people, as well as providing tangible added value to the national economy in an effort to achieve people's welfare. Since 2010 mining in the area of ​​Sangkar Puyuh, Kolok Village, Barangin District, is no longer managed by the state but by the community. Coal management is carried out by the local community in collaboration with the private sector in this case with CV. TAHITI COAL. The agreement was made in 2010 and is valid for the next ten (10) years. The research method is a sociological juridical problem approach, using primary data and secondary data collected through interviews and literature studies which are then processed through editing and coding. Then analyzed using qualitative analysis. The answer as well as the conclusion of the research obtained was the implementation of the Coal Mining Agreement that occurred between the Nan Balimo Kolok Nan Tuo Tribe as the First Party and CV. TAHITI COAL as the second Party in the Quail Cage Area of ​​Kolok Village, Barangin District, Sawahlunto City. The obstacles faced in implementing the coal mining agreement between the Nan Balimo Kolok Nan Tuo Tribe and CV. TAHITI COAL is that the agreement agreement was not obtained in a short time and the solution is to accelerate the completion of the agreement. It is recommended to CV. TAHITI COAL in order to make an agreement with the Nan Balimo Kolok Nan Tuo tribe to contain the overall provisions and regulate the agreement, it is suggested to the parties to always stick to and refer to the agreed agreement.